Entrepreneurial Intelligence Among UiTM students / Azmirull Syukree Aminudine - Aminudine, Azmirull Syukree (Faculty of Business and Management, UITM Sarawak, 2015)
Doing business can be easy or difficult to future graduates student if they choose to become an entrepreneur. It depends on their knowledge and skills in entrepreneurship. In Malaysia, there is lots of business opportunity that graduates can take as an opportunity or an option to build career in their lives. In business, the important thing is a business idea. As entrepreneur, we need to start from small businesses. Entrepreneur need to explore in that particular strategic or various locations on what they can sell and get demand from people in order to have profit. Malaysia is one of monetary player in the Asean locale. Despite the fact that Singapore has the quality in the monetary, Indonesia has the size and Thailand is great in tourism industry, yet Malaysia has the future and high potential in financial development. There are different assets that can be made and to frame a business if business people know how to look for the open doors that accessible in Malaysia. Furthermore, Malaysia is one of the best places to start up a business with a small capital. In fact, the focal people in Malaysia can enjoy the grant that provided by the government to start up the business. So, the future entrepreneurs in Malaysia can take it as opportunity to enter the market. In these matters, students need to know or aware about business opportunities in Malaysia. According to Etzkowitz (2006), the potential for future economic development increasingly lies in the university because university has the students that have many sources of new ideas. Entrepreneur can be one of the best job options to apply in career life. To create a business, there are three dimensions need to be considered by undergraduates student which are creative intelligence, analytical intelligence and practical intelligence.